2015
DOI: 10.2214/ajr.14.14265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Articular Cartilage of the Knee Joint Using an Isotropic Resolution 3D Fast Spin-Echo Sequence With Conventional and Radial Reformatted Images

Abstract: A 3D FSE sequence had improved diagnostic performance compared with 2D FSE sequences for detecting cartilage lesions within the knee joint but only when using both radial and conventional reformatted images for cartilage evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…The overall performance of our 10‐min MRI protocol for the detection and characterization of cartilage defects was similar to arthroscopy‐validated sensitivities (66–92%), specificities (39–98%), and accuracies (78–97%) of 3D MRI in adults . In contrast to the performance for the detection of cartilage defects, we found a lower performance for the characterization of partial‐thickness cartilage defects, with a sensitivity of 59%, which falls within the range of sensitivities of 50–88% that were reported in other 2D and 3D MRI studies . The lower sensitivity for the characterization, rather than detection of partial‐thickness cartilage defects in our study may be related to difficulties in differentiating surface irregularities of articular cartilage from low‐grade partial thickness defects on MRI.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The overall performance of our 10‐min MRI protocol for the detection and characterization of cartilage defects was similar to arthroscopy‐validated sensitivities (66–92%), specificities (39–98%), and accuracies (78–97%) of 3D MRI in adults . In contrast to the performance for the detection of cartilage defects, we found a lower performance for the characterization of partial‐thickness cartilage defects, with a sensitivity of 59%, which falls within the range of sensitivities of 50–88% that were reported in other 2D and 3D MRI studies . The lower sensitivity for the characterization, rather than detection of partial‐thickness cartilage defects in our study may be related to difficulties in differentiating surface irregularities of articular cartilage from low‐grade partial thickness defects on MRI.…”
Section: Discussionsupporting
confidence: 81%
“…21,23,[25][26][27][28] In contrast to the performance for the detection of cartilage defects, we found a lower performance for the characterization of partial-thickness cartilage defects, with a sensitivity of 59%, which falls within the range of sensitivities of 50-88% that were reported in other 2D and 3D MRI studies. 21,27,29,30 The lower sensitivity for the characterization, rather than detection of partial-thickness cartilage defects in our study may be related to difficulties in differentiating surface irregularities of articular cartilage from low-grade partial thickness defects on MRI. Similar to the variability of measuring the size of cartilage defects during arthroscopy, 31 the accuracy of assessing the relative depth of a defect may vary in children due to differences in the total thickness of the articular cartilage.…”
Section: Discussioncontrasting
confidence: 47%
“…When acquired in multiple planes, high-resolution 2D sequences are the clinical standard for the evaluation of cartilage pathology. 8,9 However, 3D acquisitions may provide increased sensitivity and specificity for the detection of cartilage lesions in comparison to 2D acquisitions 9,10 as they are less impacted by partial volume effects, and can take better advantage of multiplanar reformations. Fast spin echo (FSE) and spoiled gradient-recalled echo (SPGR) sequences are commonly used for the morphologic assessment of cartilage.…”
Section: Mr Sequences For Morphologic Cartilage Assessmentmentioning
confidence: 99%
“…Images with isotropic voxels also permit multi‐planar reformatting from a single acquisition. While recent studies of knee articular cartilage have found that an isotropic 3D acquisition, combined with radial and conventional (three‐plane) reformatted images, may have higher sensitivity and specificity than corresponding 2D acquisitions, 2D imaging is still considered the standard in the clinical environment.…”
Section: Radiographymentioning
confidence: 99%